In the Peaceful Mind and Self Obstinance Mother and Child Story in Muslim and Buddhist Polygamy Families - Latifah; Ary Budiyanto (STAB Kertarajasa, 2022)
Tradition and religion are often, on the one hand, used to legitimize conditions that are difficult for women, but on the other hand also offer values ​​that elevate women's dignity and position, including in the case of polygamy. Throughout history many have spoken of the various negative consequences economically, psychologically, and socially experienced by children and wives in polygamous families. But in general the narrative positions women as victims so that it does not provide a perspective of empowered women who have the power to manage their family conflicts by showing the quality of their leadership in the family and community. With content analysis, this paper examines women's biographical novels from two different religious and social backgrounds. With content analysis, this paper examines women's biographical novels from two different religious and social backgrounds. First, a collection of stories Menunggu Papa: Kisah Gadis Kecil yang Akhirnya Berdamai dengan Dirinya, which is a collection of inspiring stories based on the autobiography of Yanah Sucintani, which tells the inner journey of a child from a Chinese-Buddhist family whose father practices polygamy. Second, the novel titled Athirah by Alberthiene Endah, which is a biography of Jusuf Kalla, which tells the story of the mother's leadership in a polygamous family set in the Muslim-Bugis-Makassar society. This study has important meaning in encouraging a positive image of women as whole human beings, developing personally and contributing to society. This positive role needs to be raised more especially as a counter culture of women's representation in the world of entertainment and popular culture which widely accommodates the female stereotype. Both of these inspirational stories teach that indeed the financial independence of a polygamous mother is the initial way to be able to rule over herself and her children, but it requires persistent spirituality to be able to establish themselves as wives and mothers and lay the foundation of mentality for their children.